Transformasi pengetahuan peternak sapi melalui penyuluhan: Analisis di Kecamatan Karangpandan - Ardela Nurmastiti; Ardian Ozzy Wianto (Fakultas Pertanian Universitas Majalengka, 2025)
This study aims to analyze the transformation of knowledge among beef cattle farmers through agricultural extension services in Karangpandan Regency. In rural areas, beef cattle farming is generally traditional and managed based on inherited experience without adequate scientific support. This study used a quantitative descriptive approach with 30 respondents selected purposively. Data were collected through interviews and questionnaires. The analysis used multiple linear regression analysis to examine the influence of extension services (as educators, disseminators of information/innovation, facilitators, consultants, and supervisors) on the level of knowledge of beef cattle farmers (selecting seeds, providing appropriate feed, livestock maintenance methods, pen maintenance, and livestock health management). The results showed that most respondents were in the productive age group (31–50 years), with relatively low levels of education and varying farming experience. Farmers generally had moderate to high levels of knowledge, especially regarding pen management and animal health, while knowledge about breeding was still limited. The role of agricultural extension agents as educators, information/innovation disseminators, facilitators, and supervisors had a significant positive effect on improving livestock farmers' knowledge (p < 0.05). Meanwhile, the role of consultants did not show a significant effect. This study concludes that extension services play a strategic role in empowering and transforming the knowledge of beef cattle farmers through a participatory and needs-based approach. To improve the effectiveness and sustainability of livestock extension programs, it is recommended to strengthen the capacity of extension workers and optimize their facilitation and supervision functions.